Thymosins in multiple sclerosis and its experimental models: moving from basic to clinical application - Severa, Martina (Mult Scler Relat Disord, 2019)
Background: Multiple sclerosis (MS) afflicts more than 2.5 million individuals worldwide and this number is increasing over time. Within the past years, a great number of disease-modifying treatments have emerged; however, efficacious treatments and a cure for MS await discovery. Thymosins, soluble hormone-like peptides produced by the thymus gland, can mediate immune and non-immune physiological processes and have gained interest in recent years as therapeutics in inflammatory and autoimmune diseases. Methods: Pubmed was searched with no time constraints for articles using a combination of the keywords “thymosin/s” or “thymus factor/s” AND “multiple sclerosis”, mesh terms with no language restriction. Results: Here, we review the state-of-the-art on the effects of thymosins on MS and its experimental models. In particular, we describe what is known in this field on the roles of thymosin-α1 (Tα1) and -β4 (Tβ4) as potential anti-inflammatory as well as neuroprotective and remyelinating molecules and their mechanisms of action. Conclusion: Based on the data that Tα1 and Tβ4 act as anti-inflammatory molecules and as inducers of myelin repair and neuronal protection, respectively, a possible therapeutic application in MS for Tα1 and Tβ4 alone or combined with other approved drugs may be envisaged. This approach is reasonable in light of the current clinical usage of Tα1 and data demonstrating the safety, tolerability and efficacy of Tβ4 in clinical practice.